1983
DOI: 10.2527/jas1983.5751100x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Straightbred and Crossbred Rabbits for Milk Production and Associative Traits

Abstract: Two hundred twenty-five lactation and litter performance records from 82 does representing four genetic groups and two diets were analyzed to quantify breed, heterosis, reciprocal F1 cross and diet effects for milk production and associative traits. Doe genetic groups were New Zealand White (NN) and Californian (CC) straightbred and Californian X New Zealand White (CN) and New Zealand White X Californian (NC) reciprocal crossbreds. Pelleted diets fed to does and litters were either a commercial control or a 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 8 publications
4
31
1
Order By: Relevance
“…The highest correlations reported are for the period between birth and 21 days of age and amount to 0.90 (Lebas, 1969), 0.91 (Fortun-Lamothe andSabater, 2003) or even 0.99 (Lukefahr et al, 1983). Weight gain of the litter at a later stage is much less correlated with the milk yield in the corresponding period (Lebas, 1969).…”
Section: Estimation Based On the Growth Of The Suckling Kitsmentioning
confidence: 98%
See 1 more Smart Citation
“…The highest correlations reported are for the period between birth and 21 days of age and amount to 0.90 (Lebas, 1969), 0.91 (Fortun-Lamothe andSabater, 2003) or even 0.99 (Lukefahr et al, 1983). Weight gain of the litter at a later stage is much less correlated with the milk yield in the corresponding period (Lebas, 1969).…”
Section: Estimation Based On the Growth Of The Suckling Kitsmentioning
confidence: 98%
“…Lukefahr et al (1983) demonstrated that New Zealand White does are superior (+ 30%) to Californian does and that crossbred rabbits of both breeds are superior than the pure breeds. However, in another study, the same team determined a comparable milk production for the 4 breeds tested (Calfornian, New Zealand White, Palomino and White Satin) (McNitt and Lukefahr, 1990), which indicate that the genetic background of the particular populations is perhaps more important than the breed itself.…”
Section: Genotypementioning
confidence: 99%
“…Lukefahr et al (1983) detected a strong positive association within breed between milk production of the doe and both litter size and weight at 21 d of age. In intensive rabbit meat production, it is common to use crossbred does from lines selected for litter size and thereby indirectly improve milk yield (Garreau et al, 2004).…”
mentioning
confidence: 96%
“…An increase in litter size by one kit born alive increased weekly milk yield by 49.21 g/wk; this confirmed the positive relationship between litter size and milk production in maternal rabbit lines already reported in the literature. Lukefahr et al (1983) reported a correlation coefficient of 0.78 between total 21 d lactational yield and litter size at 21 d. Iraqi and Youssef (2006) estimated that an increase in litter size by one kit resulted in an increase by 42.9, 84.4, 102.4, 84.6 and 306.9 g of milk for the 1 st , 2 nd , 3 rd , 4 th week and total milk yield, respectively. Other studies confirmed this positive phenotypic relationship between litter size and milk production in rabbits.…”
Section: Effect Of Nba and Dw On Milk Traitsmentioning
confidence: 99%
See 1 more Smart Citation